Avaliação do desempenho nas atividades cotidianas de idosos participantes de um programa de convivência social - Sousa, Hisllaeny Almeida (Universidade Federal do Tocantins, 2020)
Introduction: Functional capacity is the ability of the elderly to lead their own lives or take care of themselves, and maintaining their autonomy and independence is an important factor. The impairment of autonomy and independence results in functional disability, which is an important health problem of the elderly population in Brazil and with regard to retarding functional limitations, the practice of social activities becomes a good ally to an active and healthy aging. Objective: Present the article “Functional limitation in activities of daily living and associated factors in the elderly at the University of Maturity”. Method: Scientific article published in the journal Humanities and Innovation, in the year 2019. Quantitative research with cross-sectional design whose objective was to evaluate the living, health and nutrition conditions of elderly participants of the University of Maturity of the Federal University of Tocantins (UMA / UFT). Result: The present article revealed that most of the elderly participants at the University of Maturity are independent, and the limitation to perform basic activities (ABVD) and instrumental daily life (IADL) was 3.7% and 29.6%, respectively. . There was a statistical association between ABVD and cognitive decline and between IADL with age and multimorbidity. The inclusion of the elderly in programs such as UMA enables the reduction of the impact of the loss of functional skills on quality of life. Conclusion: It was concluded that it was possible to present the article published in the journal Humanities and Innovation and it is emphasized that the data presented in the article cannot be extrapolated to the elderly population of the city of Palmas, as it refers to a convenience sample.